Macrozoobenthos as bioindicator of ecological status in Tanjung Pasir Coastal, Tangerang District, Banten Province, Indonesia - ASEP SAHIDIN; ZAHIDAH ZAHIDAH; HETI HERAWATI; YUSLI WARDIATNO; ISDRADJAD SETYOBUDIANDI; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2018)
Sahidin A, Zahidah, Herawati H, Wardiatno Y, Setyobudiandi I, Partasasmita R. 2018. Macrozoobenthos as bioindicator of ecological status in Tanjung Pasir Coastal, Tangerang District, Banten Province, Indonesia. Biodiversitas 19: 1123-1129. The existence of macrozoobenthos organism allow for bioindicator of ecological status and detected water pollution in coastal environment with observing the response, diversity, and abundance. The one of biological method for water quality analysis is AZTI Marine Biotic Index (AMBI). This research aims to determine water quality status in Tanjung Pasir water coastal Tangerang, Banten. The research was conducted in April - August 2014 in Tanjung Pasir Coastal, Tanggerang, Banten with purposive sampling method and be forwarded with water pollution analysis with AZTI Marine Biotic Index (AMBI) model. The research showed 4.552 individual of macrozoobenthos found divided into 52 species with the average of diversity amount 634 ind./m2 with dominated by bivalve species Nuculana bicuspidate  22.89%, it is a bivalve an extreme species that can live in waters with very low oxygen concentrations and hight pollution. The result of AMBI (4.01 to 5.02) indicates water pollution in Tanjung Pasir Coastal classified in medium-heavy pollution and concentred in coastal zone. Polychaeta is a key bioindicator in the determination of water pollution and ecological status in Tanjung Pasir coastal.